Implications of Unregistered Marriage for Women: Profitable or Detrimental - Wicaksono, Alfiya (NORMA, 2021)
In Islam, marriage is a form of worship recommended by the Prophet Muhammad, so that the law is Sunnah. Marriage is something very sacred where a man and woman are united by a marriage bond and become a couple as husband and wife. Marriage is declared valid if it is carried out following religious law. In Indonesia, exist the term unregistered marriage. However, Indonesia's law considers marriage invalid if the KUA institution does not register the marriage even though it has carried out a marriage procession according to its religious law. This certainly has implications, both positive and negative, for couples, especially women. This is a normative legal research. The result of this study is it can be concluded that unregistered marriage is very detrimental to womenKeywords: Unregistered Marriage, Law, Detrimental